2020
DOI: 10.3390/nu12061762
|View full text |Cite
|
Sign up to set email alerts
|

Eating Vegetables First at Start of Meal and Food Intake among Preschool Children in Japan

Abstract: Eating behavior is an important aspect for dietary quality and long-term health. This study examined associations between eating vegetables first at a meal and food intakes among preschool children in Tokyo, Japan. We used cross-sectional data of 135 preschool children from seven nursery schools in Adachi City, Tokyo, Japan. Caregivers completed a survey on child’s eating behaviors and a diet questionnaire. Linear regression was used to examine frequency of eating vegetables first at a meal and food intakes; p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
(38 reference statements)
2
2
0
2
Order By: Relevance
“…School-level promotion of eating vegetables first at meals was associated with better eating behaviours related to vegetable intake among children. This finding is consistent with the result of a previous study examining the effect of the individual-level variable of eating vegetables first at meals on diet [ 23 ]. A study among Japanese preschool children showed that children who more often ate vegetables first at meals consumed 148 g of vegetables per 1000 kcal, which was much higher than the 68.0 g of vegetables per 1000 kcal consumed by children who rarely or never ate vegetables first at meals [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…School-level promotion of eating vegetables first at meals was associated with better eating behaviours related to vegetable intake among children. This finding is consistent with the result of a previous study examining the effect of the individual-level variable of eating vegetables first at meals on diet [ 23 ]. A study among Japanese preschool children showed that children who more often ate vegetables first at meals consumed 148 g of vegetables per 1000 kcal, which was much higher than the 68.0 g of vegetables per 1000 kcal consumed by children who rarely or never ate vegetables first at meals [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with the result of a previous study examining the effect of the individual-level variable of eating vegetables first at meals on diet [ 23 ]. A study among Japanese preschool children showed that children who more often ate vegetables first at meals consumed 148 g of vegetables per 1000 kcal, which was much higher than the 68.0 g of vegetables per 1000 kcal consumed by children who rarely or never ate vegetables first at meals [ 23 ]. In our study, we found that school-level promotion of eating vegetables first at meals was associated with higher willingness to eat vegetables and an increase in the kinds of vegetables children would eat.…”
Section: Discussionsupporting
confidence: 92%
“…The consumption of vegetables first may have greater benefits than other alternatives. A Japanese study showed that children who ate vegetables first had a higher total vegetable intake than those who did not eat vegetables first ( 29 ). A study in the United States reported similar results ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Eating vegetables first led to increased vegetable intake and reduced food energy intake ( 10 ). The vegetable intake of children who ate vegetables first was 93% higher than of that in children who do not often or never eat vegetables first ( 29 ). In addition to children, eating vegetables also has many advantages for adults.…”
Section: Discussionmentioning
confidence: 99%
“…Mokslinių tyrimų duomenys atskleidė, kad dažnesnis vaisių ir daržovių vartojimas kūdikystėje yra reikšmingai susijęs su didesniu vaisių ir daržovių pasirinkimu ir didesniu šių produktų vartojimu sulaukus šešerių metų. Ir, atvirkščiai, nesveikas mitybos elgesys ankstyvoje vaikystėje, toks kaip cukrumi saldintų gėrimų vartojimas, gali padidinti šių produktų vartojimą vėlesniame vaikystės etape ir didinti nutukimo riziką ateityje [1,2,6].…”
Section: įVadasunclassified